TRENDS IN GLOBAL CARBON DIOXIDE EMISSIONS IN THE ATMOSPHERE - Upadhyaya, Bhawana; Patel, Priyanka - (Innovare Journal of Sciences, 2016)
This study is an attempt to identify theÂ level of increase carbon dioxide gas emission and atmospheric temperature in the last 5 years. National Geographic noted that there is a exchange of energy between the source (the Sun), & the Earth's surface, the Earth's atmosphere, and the ultimate sink outer space. The ability of the atmosphere to capture and recycle energy emitted by the Earth surface is the defining characteristic of the Green House Effect.CO2, CH4, N2O, H2O are green house gases which are responsible for Green House Effect. Out of all these CO2 is mainly responsible for Green House Effect. Therefore a need was felt to study the variations in carbon dioxide concentration to be fundamental factor influencing climatic variations over this time scale. In this study, researchers have chosen only CO2 gas and its increasing value worldwide. Study reveals that the recent phenomenon of global warming has been attributed primarily due to increasing atmospheric carbon dioxide concentration in Earth's atmosphere. The research reveals the truth from that the concentration of carbon dioxide and temperature in the atmosphere have Â increased duringÂ past five years.